Image, Knife, and Gluepot Early Assemblage in Manuscript and Print - Rudy, Kathryn M. (Open Book Publishers, 2019)
"In this ingenious study, Kathryn Rudy takes the reader on a journey to trace the birth, life and afterlife of a Netherlandish book of hours made in 1500. Image, Knife, and Gluepot painstakingly reconstructs the process by which this manuscript was created and discusses its significance as a text at the forefront of fifteenth-century book production, when the invention of mechanically-produced images led to the creation of new multimedia objects. Rudy then travels to the nineteenth century to examine the phenomenon of manuscript books being pillaged for their prints and drawings: she has diligently tracked down the dismembered parts of this book of hours for the first time. Image, Knife, and Gluepot also documents Rudy's twenty-first-century research process, as she hunts through archives while grappling with the logistics and occasionally the limits of academic research. This is a timely volume, focusing on questions of materiality at the forefront of medieval and literary studies. Beautifully illustrated throughout, its use of original material and its striking interdisciplinary approach, combining book and art history, make it a significant academic achievement. Image, Knife, and Gluepot is a valuable text for any scholar in the fields of medieval studies, the history of early books and publishing, cultural history or material culture. Written in Rudy's inimitable style, it will also be rewarding for any student enrolled in a course on manuscript production, as well as non-specialists interested in the afterlives of manuscripts and prints. The Royal Society of Edinburgh has generously contributed to this Open Access publication. Due to the number and quality of the images in this book, we have provided the option of a more expensive hardback edition, printed on the best quality paper available, in order to present the images as clearly and beautifully as possible. We hope this range of options - the freely available PDF, HTML and XML editions; the economically priced EPUB, MOBI and paperback editions; and the more expensively printed hardback - will satisfy everyone. Furthermore the HTML edition allows readers to magnify the images of the manuscripts displayed in the book. "